Synthesis and characterization of photocrosslinkable gelatin and silk fibroin interpenetrating polymer network hydrogels - Xiao, Wenqian; He, Jiankang; Nichol, Jason W.; Wang, Lianyong; Hutson, Ché B.; Wang, Ben; Du, Yanan; Fan, Hongsong; Khademhosseini, Ali (Acta biomaterialia, 2011)
To effectively repair or replace damaged tissues, it is necessary to design scaffolds with tunable structural and biomechanical properties that closely mimic the host tissue. In this paper, we describe a newly synthesized photocrosslinkable interpenetrating polymer network (IPN) hydrogel based on gelatin methacrylate (GelMA) and silk fibroin (SF) formed by sequential polymerization, which possesses tunable structural and biological properties. Experimental results revealed that IPNs, where both the GelMA and SF were independently crosslinked in interpenetrating networks, demonstrated a lower swelling ratio, higher compressive modulus and lower degradation rate as compared to the GelMA and semi-IPN hydrogels, where only GelMA was crosslinked. These differences were likely caused by a higher degree of overall crosslinking due to the presence of crystallized SF in the IPN hydrogels. NIH-3T3 fibroblasts readily attached to, spread and proliferated on the surface of IPN hydrogels, as demonstrated by F-actin staining and analysis of mitochondrial activity (MTT). In addition, photolithography combined with lyophilization techniques was used to fabricate three-dimensional micropatterned and porous microscaffolds from GelMA–SF IPN hydrogels, furthering their versatility for use in various microscale tissue engineering applications. Overall, this study introduces a class of photocrosslinkable, mechanically robust and tunable IPN hydrogels that could be useful for various tissue engineering and regenerative medicine applications.